2020
DOI: 10.3389/fnhum.2020.557534
|View full text |Cite
|
Sign up to set email alerts
|

Robust EEG-Based Decoding of Auditory Attention With High-RMS-Level Speech Segments in Noisy Conditions

Abstract: The attended speech stream can be detected robustly, even in adverse auditory scenarios with auditory attentional modulation, and can be decoded using electroencephalographic (EEG) data. Speech segmentation based on the relative root-mean-square (RMS) intensity can be used to estimate segmental contributions to perception in noisy conditions. High-RMS-level segments contain crucial information for speech perception. Hence, this study aimed to investigate the effect of high-RMS-level speech segments on auditory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(21 citation statements)
references
References 61 publications
1
20
0
Order By: Relevance
“…Brain activities related to attention also show similar mechanisms to that of humans who confine their attention to the behaviorally relevant information and inhibit the processing of irrelevant information (Zanto and Gazzaley, 2009 ; Foxe and Snyder, 2011 ; Vanthornhout et al, 2019 ). However, we are not aware of other studies on the AAD tasks, using both linear and non-linear models (Mirkovic et al, 2015 ; O'Sullivan et al, 2015 ; Van Eyndhoven et al, 2016 ; Deckers et al, 2018 ; Ciccarelli et al, 2019 ; Bednar and Lalor, 2020 ; Cai et al, 2020 ; Wang et al, 2020 ; Vandecappelle et al, 2021 ), which can emphasize more important and discriminative components of the EEG signal for the AAD based on the audio attention vector.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Brain activities related to attention also show similar mechanisms to that of humans who confine their attention to the behaviorally relevant information and inhibit the processing of irrelevant information (Zanto and Gazzaley, 2009 ; Foxe and Snyder, 2011 ; Vanthornhout et al, 2019 ). However, we are not aware of other studies on the AAD tasks, using both linear and non-linear models (Mirkovic et al, 2015 ; O'Sullivan et al, 2015 ; Van Eyndhoven et al, 2016 ; Deckers et al, 2018 ; Ciccarelli et al, 2019 ; Bednar and Lalor, 2020 ; Cai et al, 2020 ; Wang et al, 2020 ; Vandecappelle et al, 2021 ), which can emphasize more important and discriminative components of the EEG signal for the AAD based on the audio attention vector.…”
Section: Discussionmentioning
confidence: 97%
“…EEG provides a non-invasive means of investigating cortical activity with high temporal resolution and is a realistic option for BCI applications. Various experiments have verified the feasibility of decoding the selective attention in a multispeaker environment using EEG (Choi et al, 2013;Mirkovic et al, 2015;O'Sullivan et al, 2015;Van Eyndhoven et al, 2016;Deckers et al, 2018;Bednar and Lalor, 2020;Cai et al, 2020Cai et al, , 2021Wang et al, 2020). The decoding of selective auditory attention from non-invasive EEG signals is of interest in BCI and auditory perception research and can mainly be divided into linear and non-linear approaches.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 2A shows the RMS level of a continuous utterance and higher- and lower-RMS-level segments within this sentence. This segmentation threshold (i.e., –10 dB relative to the RMS level of the whole sentence) was determined according to the distribution of perceptual information in different RMS-level–based speech segments, which was originally proposed in Kates and Arehart (2005) and extensively studied in many behavioral and electrophysiological experiments (e.g., Kates and Arehart, 2005 ; Chen and Loizou, 2011 , 2012 ; Chen and Wong, 2013 ; Wang et al, 2019 , 2020a , b ; Wang, 2021 ). Previous studies have found that higher-RMS-level–speech segments mainly contained the vowels and transitions between vowels and consonants, whereas lower-RMS-level speech segments carried the weak consonants and silent gaps of the continuous utterance ( Chen and Loizou, 2011 , 2012 ; Chen and Wong, 2013 ).…”
Section: Methodsmentioning
confidence: 99%
“…Higher-RMS-level speech segments contained the voicing parts of the sentences (i.e., the most proportion of vowels and vowel–consonant transitions), whereas most silent gaps and weak consonants were located in lower-RMS-level speech segments ( Chen and Loizou, 2011 ; Chen and Wong, 2013 ). Previous studies also demonstrated that higher- and lower-RMS-level–based speech segments had different effects on the encoding and decoding of the target speech from the corresponding EEG signals ( Wang et al, 2019 , 2020a , b ). Moreover, in cases where the listeners were required to maintain their attention on the target speech stream, the AAD sensitivity and accuracy could be improved by using the time-variant segmented model to decode different types of RMS-level–based speech segments ( Wang, 2021 ).…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation